METHODOLOGY OF UTILIZING THE TEACHING OF ISLAMIC LAW AND ITS PRINCIPLES IN ENHANCING MODERATION: "A CRITICAL STUDY FOR THE CONCEPT AND APPLICATIONS" - al-Assaf, Adnan M. (European Scientific Journal, ESJ, 2013)
It is an essential necessity in the contemporary world to enhance moderation and tolerance, as terrorism and mutual intolerance have become major problems that threaten the foundations of world peace. This situation has resulted in the emergence of a dramatic increase in research interest in various field of study to investigate the reasons behind this dangerous phenomenon, and to try to identify solutions to remedy the problem. Although the response of Islamic researchers has been broad, the general tone seems defensive and apologetic, at times to the point of disregarding the practicalities of treating the problem. In view of the facts outlined above, this project aims to shed light on methods of utilizing the teaching of Islamic Law and its Principles in a way that allows graduates to be more effective in disseminating the values of moderation and challenging intolerance and terrorism in our societies. Hence, the longterm goals of this project are to assist in spreading general awareness in this concern, and tolerant attitudes, as well as supporting the concept of coexistence and supporting human rights. The specific objectives of this project are to establish a practical, comprehensive program to utilize the teaching of Islamic Law and its Principles in enhancing moderation and tolerance. The outcome of this research is expected to influence a large number of Islamic studies graduates and youth in the Muslim world. Improving the performance of faculties of Sharicah, Islamic Studies, is another important goal of this project. Literature Review: reviewing the available literature of Islamic Studies in this respect, one can argue that it is difficult to find research that provides a clear method to enhance moderation and tolerance from the academic field targeted in this project. However, there are several published pieces of research which are related to the scope of this research in Islamic literature. For example, the papers presented at the Islamic conference of: "Moderation is a Way of Life ", which was held in Kuwait in 23/5/2005. These research papers represent a positive contribution to the field by studying the concept of moderation and clarifying its application in Islamic sources, as well as in the different fields of Islamic Law. This is in addition to the relationship between moderation and civilization, and its role in media. Further, some of these efforts were devoted to shed light on intolerance in particular. They assess its causes and solutions. However, there is still a lack of research relating to the question: How can we utilise teaching Islamic Law and its Principles in enhancing moderation and tolerance? Research Method: The researcher will undertake the following methods to achieve the objectives of this project. Firstly, the concept of moderation is assessed by consulting the sources of Islam to determine its relevance. Secondly, the means of enhancing moderation in thinking and practice are derived from the sources of Islamic Law and its Principles, by applying the derived elements of moderation. Thirdly, applicable conclusions and recommendations are determined as a conclusion, to outline the main features of the objective methodology.